Effect of H3PO4 Concentration and Particle Size of the Eggshell Used in Laying Hens Fed on Bone and Blood - S. Kismiati; T. Yuwanto; Z. Zuprizal; S. Supadmo (International Journal of Science and Engineering, 2013)
The objective of this research was to evaluate the effect of H3 PO4 concentrations and particle size of eggshell used in the feed of laying hens on bone and blood profiles. Ninety-six laying hens (Isa Brown strain) age 25 weeks were kept in individual battery cage and divided into 8 groups randomly. Group 1 was fed using eggshell with out H3PO4 and particle size of <1 mm (feed 1 ), group 2 was fed using eggshell that has been soaked in H3PO4 3% and particle size of <1 mm (feed 2), group 3 were fed using eggshell that has been soaked in H3PO4 4% and particle size of <1 mm (feed 3), group 4 was fed using eggshell that has been soaked in H3PO4 5% and particle size of <1 mm (feed 4), group 5 was fed using eggshell that has been soaked in H3PO4 and particle size of <3 mm (feed 5 ), group of 6 was fed using eggshell that has been soaked in H3PO4 3% and particle size of <3 mm (feed 6), group 7 was fed using eggshell that has been soaked in H3PO4 4 % and particle size of <3 mm (feed 7) and a group of 8 was fed using eggshell that has been soaked in H3PO4 5% and particle size of <3 mm (feed 8). A Completely Randomized Design patterns factorial 4 x 2 x 3 was used in this research. Result of this research showed that had no interaction effect (P>0.05) between the H3PO4 concentration and particle size of eggshell on weight, volume, diameter of tibia bone and calcium and phosphorus content of the blood. The concentration of H3PO4 or particles size also had no effect (P>0.05) on all variables. Doi: 10.12777/ijse.5.1.12-14 [How to cite this article: Kismiati, S., Yuwanta, T., Zuprizal, and Supadmo. (2013). Effect of H3PO4 Concentration and Particle Size of the Eggshell Used in Laying Hens Fed on Bone and Blood. International Journal of Science and Engineering, 5(1),6-11. Doi: 10.12777/ijse.5.1.12-14]